Association between GLP-1 RAs and DPP-4 inhibitors with biliary disorders: pharmacovigilance analysis - He, Long; Li, Jinwei; Cheng, Xiong; Luo, Li; Huang, Yilan (Frontiers in Pharmacology, 2025)
Background and AimsIncretin-based therapies, including glucagon-like peptide 1 receptor agonists (GLP-1 RAs) and dipeptidyl peptidase-4 (DPP-4) inhibitors, are essential treatments in diabetes management due to their efficacy in glycemic control and the additional benefits of GLP-1 RAs, which include cardiovascular and renal protection. However, concerns about potential associations with biliary disorders necessitate ongoing pharmacovigilance. This study analyzes the link between these drugs and biliary adverse events (AEs) using the FDA Adverse Event Reporting System (FAERS) to enhance clinical safety.MethodsWe extracted AE data for GLP-1 RAs and DPP-4 inhibitors from FAERS between Q1 2013 and Q1 2024 using OpenVigil 2.1. Analytical methods such as the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayesian Geometric Mean (EBGM) were employed to assess AE risk.ResultsA search of biliary disorders by standard MedDRA analytical queries (SMQs) identified 2,215 reports of biliary AEs, with 1,709 related to GLP-1 RAs and 506 to DPP-4 inhibitors. DPP-4 inhibitors showed a significant association with biliary disorders (ROR, 3.09; 95% CI, 2.83–3.37), particularly sitagliptin (ROR, 3.46; 95% CI, 3.13–3.83). Although the overall association for GLP-1 RAs (ROR, 1.60; 95% CI, 1.52–1.68) was not significant, semaglutide (ROR, 4.06; 95% CI, 3.76–4.39) and liraglutide (ROR, 3.88; 95% CI, 3.50–4.29) indicated a notable risk. The SMQ subgroup analyses of sitagliptin, semaglutide, and liraglutide with the SMQ subgroup categories of “biliary tract disorders,” “gallbladder related disorders,” “gallstone related disorders,” and “infectious biliary disorders’ demonstrated a statistically significant correlation. Notably, liraglutide, alogliptin, sitagliptin, and linagliptin were linked to “biliary malignant tumors” with statistical significance. The proportion of serious outcomes was higher for DPP-4 inhibitors (n = 389, 76.88%) compared to GLP-1 RAs (n = 881, 51.55%).ConclusionDPP-4 inhibitors are potentially linked to biliary disorders, warranting vigilance. While the overall association for GLP-1 RAs was not significant, specific drugs like semaglutide, liraglutide, and sitagliptin showed concerning signals, suggesting a need for heightened awareness among clinicians regarding the risk of biliary AEs.